Análise do equilíbrio morfológico em rios regularizados : modelagem matemática unidimensional do transporte de sedimentos no rio São Francisco - Vinícius Roman (2004)
The rivers naturally transport sediment from the uplands to the ocean. When sediment transport equilibrium is broken by the construction of a dam in the river, the three most significative impacts are: (i) retention of sediment yield from the river basin until the dam section; (ii) reduction of sediment discharge donstream from the dam, increasing the erosive power of the water in the river bed; and (iii) reduction of the flood peaks downstream the dam, decreasing the sediment transport power of the stream. These impacts induce certain instability in the river bed which adjusts itself to the new conditions and cause a new equilibrium situation later. This work investigates the adjustment in river morphology downstream the dam using one dimensional mathematical modeling, of stream, sediment transport and river morphological changes due to the erosion and deposition of sediment. The study was developed in a river basin where the dam already exists. The methodology was described for the recomposition of natural sediment discharge series and simulated considering the existence and non-existence of the dam. The software HEC-6 was used for the one dimensional modeling process. The comparison between this two hypotesis was tested using the São Francisco river basin downstream from Três Marias dam, and have demonstrated that the dam does not affect in the sediment mass balance in the long term, at least in an extension of 350 kilometers between the Três Marias dam and São Francisco town.